Community mental health teams for older people: variations in case mix and service receipt (I). (9th September 2014) - Tucker, Sue; Wilberforce, Mark; Brand, Christian; Abendstern, Michele; Crook, Anthony; Jasper, Rowan; Stewart, Karen; Challis, David
<x xml:space="preserve">Abstract</x> Objectives The study sought to identify the characteristics of community‐dwelling older people supported by community mental health teams (CMHTs) in England and, in particular, to determine whether there is a common threshold for CMHT entry and/or a core client group. Methods Data were collected about a random sample of 15 CMHTs' caseloads, including information about their sociodemographic characteristics, physical health, dependence, mental health, risks and service receipt. The sample was divided into 16 subgroups of people with similar needs for care (case types), and differences between teams were explored. Results Information was obtained for 1396 patients. Just under half had a functional mental health problem, slightly over a third an organic disorder, seven per cent both, and nine per cent no diagnosis. Considerable variation was found in teams' caseloads, and there was no evidence of a common caseload threshold. Two of the commonest case types represented people with functional diagnoses who were independent in activities of daily living (ADL) and had no/low levels of challenging behaviour. Another representing people with organic/mixed diagnoses, ADL dependence, challenging behaviour and at least one medium risk was also fairly common. The two case types that represented patients with the most complex needs accounted for more than a quarter of some teams' caseloads but less than a tenth of others. Conclusions It is wrong to assume that CMHTs all have similar caseloads. Commissioners must ensure that the network of services provided can meet the needs of all eligible patients, whilst more research is required on who such teams should target. Copyright © 2014 John Wiley & Sons, Ltd.